Continuum approximation modeling of transit network design considering local route service and short-turn strategy. (November 2018) - Chen, Jingxu; Liu, Zhiyuan; Wang, Shuaian; Chen, Xuewu
Highlights: A continuum approximation modeling for transit network design is proposed. Two complementary transit services from different planning stages are addressed. Spatial and temporal heterogeneity of travel demand is concerned. Comparative analysis on different transit network configurations is performed. Sensitivity analysis on demand, service boundary and cost parameters is performed. Abstract: This paper proposes a continuum approximation (CA) modeling framework to optimize the hybrid transit network designed with grids in the central district and hub-and-spoke structure in the periphery. Two CA models are formulated incorporating the local route service and the short-turn strategy respectively. The transit network configuration is optimized through minimizing the objective functions, which consider costs pertinent to passengers and operating agency. The decision variables include service boundary, spacings and headways of the regular service and the complementary services. Numerical experiments show that the performances of CA models with different complementary services are quite distinct under various demand scenarios.